PENELITIAN TINDAKAN KELAS DALAM PEMBELAJARAN DI PERGURUAN TINGGI - Bararah Ibrahim (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
Action researh has been considered as an appropriate and effective mean to integrate between educational research and teaching practice. Action research has also been considered effective in developing professional capacity of teacher or lecturer and at the same time improve teaching-learning process. Action research has widespreadly used in educational research and teaching practices, however a lot of teachers or lecturers still have not understood the process and relized the benefit of the action research properly. Action research is a learning process that run in a complete cycle starting from planning, taking action, observation, and reflection sistimatically. Action research is not a static process, but it is a dynamic teaching experience. Action research is a metod and process of learning and knowing through action and experience. Therefore, the meaning of action research in a University is often summarized as a self learning that aimed to change social condition, improve teaching-learning process and improve quality of curriculum in a university. Â Key words: action researchÂ